(3UfGY GdJGQjN NdGd KdGKI bQhf (B/s - (3GdYhjO, YHO GdYRjR Hf SYhOs 1975- ((3GdchjJ (B:s (3ecJHI BaGb ddfTQ,s, 2016)
(3UfGY GdJGQjN NdGd KdGKI bQhf bUU YLjHI hedjFI HGdCMOGK Yf CfGS eKdfG YGThG bHdfG hefge ef YGUQfGg Edi hbJ bQjH cGfJ geJge eKd GdLHGd cja cGHOh GdeTbI hGdYfGA aj SHjd GdMUhd Ydi GdYde hOaYh ef ChbGJge hCehGdge hCfaSge GdTjA GdcKjQ aefge ef de jJNda Yf OQSg hgh aj UHjMI RhGLg, hefge ef dG jfGe hdG jZeV dg Laf MJi jage GdeSCdI GdJj CYjJg(B. s
(3HHdjhLQGajI (B: (3UaMI (B441-450.s
Keywords: (3JQGLe hSjQs -- (3GdbGOI hGdeacQhfs -- (3GdYGedhf GdOjfjhfs